2020
DOI: 10.1159/000511268
|View full text |Cite
|
Sign up to set email alerts
|

Update on Lupus Nephritis: Looking for a New Vision

Abstract: Lupus nephritis (LN) is one of the most common manifestations of systemic lupus erythematosus (SLE), affecting approximately 40% of patients with lupus. It represents a major risk factor for morbidity and mortality, and 10% of patients with LN will develop end-stage kidney disease (ESKD). Therefore, there are a number of areas for improvement in the field of LN such as the search for new clinical biomarkers with a more accurate correlation with lupus activity and the redefinition of the histological classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 100 publications
1
52
0
3
Order By: Relevance
“…The mortality is greater in patients with SLE and nephritis as compared to patients with SLE without nephritis. 1 Although recent studies show a decrease in the incidence of patients requiring renal replacement therapy for lupus nephritis (LN), 2 we must not forget that LN occurs in 30-45% of SLE patients, and 10-25% of them will develop endstage renal disease (ESRD) 3,4 over the course of their disease.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality is greater in patients with SLE and nephritis as compared to patients with SLE without nephritis. 1 Although recent studies show a decrease in the incidence of patients requiring renal replacement therapy for lupus nephritis (LN), 2 we must not forget that LN occurs in 30-45% of SLE patients, and 10-25% of them will develop endstage renal disease (ESRD) 3,4 over the course of their disease.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of novel and traditional biomarkers has enhanced the identification of activity patterns. 56 Combined monitoring of 24-h proteinuria and serum IL-21, in parallel, would increase the power of differential diagnosis of active and inactive LN to 98% as compared to serum IL-21 (sensitivity: 70%) or 24-h proteinuria (sensitivity: 93%) alone. This may result from the different mechanisms of both biomarkers, so that those two markers reflect different aspects of LN activity.…”
Section: Discussionmentioning
confidence: 99%
“…The data released by Chinese SLE treatment and research group (CSTAR) showed that the global average prevalence of SLE was 12-39/100,000, and the prevalence of SLE in China was 30-70/100,000, which ranked second in the world (19). SLE patients have a 50% chance of developing LN, and the degree of kidney involvement directly affects the prognosis of SLE (20). So, it is important to understand the pathogenesis, related markers, and the treatment of LN.…”
Section: Discussionmentioning
confidence: 99%